Re-Collecting Black Hawk : Landscape, Memory, and Power in the American Midwest - Brown, Nicholas A.; Kanouse, Sarah E. (Book collections on Project MUSE., 2015)
The name Black Hawk permeates the built environment in the upper midwestern United States. It has been appropriated for everything from fitness clubs to used car dealerships. Makataimeshekiakiak, the Sauk Indian war leader whose name loosely translates to "Black Hawk," surrendered in 1832 after hundreds of his fellow tribal members were slaughtered at the Bad Axe Massacre. Re-Collecting Black Hawk examines the phenomena of this appropriation in the physical landscape, and the deeply rooted sentiments it evokes among Native Americans and descendants of European settlers. Nearly 170 original pho